Enlarged and Enhancing Optic Nerves in Advanced Glial Fibrillary Acidic Protein Meningoencephalomyelitis. Issue 3 (September 2019) - White, Daniel; Mollan, Susan P.; Ramalingam, Satheesh; Nagaraju, Santhoosh; Hayton, Tom; Jacob, Saiju
Abstract : Abstract: A 36-year-old woman presented with intermittent fever, nausea and vomiting, generalized polyarthralgias, and bilateral optic disc swelling. She had a history of difficult-to-control myasthenia gravis since the age of 18 years. Lumbar puncture demonstrated a normal opening pressure; cerebrospinal fluid (CSF) was remarkable for high protein, low glucose, and a mononuclear pleocytosis. Although initial MRI of the brain was normal, a repeat study 8 weeks later revealed enlarged and enhancing bilateral intraorbital and intracranial optic nerves. After a nondiagnostic brain biopsy, a CSF sample tested positive for antibodies to glial fibrillary acidic protein (GFAP). Findings in this case indicate that optic nerve swelling encountered in GFAP meningoencephalomyelitis is more likely due to optic nerve inflammation rather than elevated intracranial pressure.